The Cost of Routine Follow-Up in Total Joint Arthroplasty and the Influence of These Visits on Treatment Plans - Hendricks, Thomas J.; Chong, Alexander C.M.; Cusick, Robert P. (Kansas Journal of Medicine, 2019)
Introduction. Many physicians recommend annual or biennial visits after total hip and knee arthroplasty (THA and TKA). This study sought to establish the cost of a post-operative visit to both the health care system and patient and identify if these visits altered patient management. Methods. A prospective cohort study was conducted using patients presenting for follow-up after THA or TKA from April through December 2016. All surgeries were performed by a single orthopaedic surgeon in Wichita, Kansas. All eligible subjects that met the inclusion criteria received and completed a questionnaire about the personal cost of the visit and their assessment of their function and outcome after total joint arthroplasty. The physician also completed a questionnaire that examined the cost of the visit to the health care system and whether the clinical or radiographic findings altered patient management. Results. Fifty-six patients participated with an average length of follow- up of 4.5 ± 4.1 years since surgery. The average patient cost was 135.20 ± 190.53 (range, 1.65 - 995.88), and the average visit time for the patient was 3.9 ± 2.9 hours. Eighty percent of patients reported no pain during the clinic encounter, and 11% reported loss of function. Eighty-four percent thought the visit was necessary. Physician time for each visit lasted 12.9 ± 3.7 minutes (range, 10 - 20 minutes). Only 9% of patient encounters resulted in an alteration in patient management. This occurred at an average follow-up time of 3.6 ± 1.8 years after the index procedure. The average cost of each visit to the health care system at large was 117.31 ± 60.53 (range, 93.90 - 428.28). Conclusions. The findings of this study advise total joint patients and orthopaedic surgeons regarding the cost of routine post-operative appointments and whether these visits alter patient management. The majority of the routine follow-up visits after THA and TKA did not result in an alteration in patient management, but added substantial cost to the health care system. Kans J Med 2018;11(3):59-66.